2023
DOI: 10.20517/cdr.2023.21
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing the value of TCTP in breast cancer treatment resistance: an opportunity for personalized therapy

Abstract: Early identification of breast cancer (BC) patients at a high risk of progression may aid in therapeutic and prognostic aims. This is especially true for metastatic disease, which is responsible for most cancer-related deaths. Growing evidence indicates that the translationally controlled tumor protein (TCTP) may be a clinically relevant marker for identifying poorly differentiated aggressive BC tumors. TCTP is an intriguing protein with pleiotropic functions, which is involved in multiple signaling pathways. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 112 publications
0
1
0
Order By: Relevance
“…The finding suggested that elevated levels of TCTP expression are indicative of increased tumor invasiveness and poorer clinical prognosis [ 27 ]. Simultaneously, a growing body of evidence has suggested that TCTP can hold promise as a clinically relevant biomarker for the identification of low-differentiated and invasive breast cancer [ 134 , 135 ].…”
Section: Expression and Targeted Application Of Tctp In Cancermentioning
confidence: 99%
“…The finding suggested that elevated levels of TCTP expression are indicative of increased tumor invasiveness and poorer clinical prognosis [ 27 ]. Simultaneously, a growing body of evidence has suggested that TCTP can hold promise as a clinically relevant biomarker for the identification of low-differentiated and invasive breast cancer [ 134 , 135 ].…”
Section: Expression and Targeted Application Of Tctp In Cancermentioning
confidence: 99%